Early Management of Acute Spinal Cord Injury—Part I: Initial Injury to Surgery - Sacino, Amanda; Rosenblatt, Kathryn (Journal of Neuroanaesthesiology and Critical Care, 2019)
Acute spinal cord injury is a devastating event associated with substantial morbidity worldwide. The pathophysiology of spinal cord injury involves the initial mechanical trauma and the subsequent inflammatory response, which may worsen the severity of neurologic dysfunction. Interventions have been studied to reduce the extent of primary injury to the spinal cord through preventive measures and to mitigate secondary insult through early specialized care. Management, therefore, is multifold, interdisciplinary, and begins immediately at the time of injury. It includes the trauma triage, acute management of the circulatory and respiratory systems, and definitive treatment, mainly with surgical decompression and stabilization.
Keywords: airway management; bradycardia; blood pressure targets; intraoperative neuromonitoring; neurogenic shock; respiratory arrest; resuscitation; spinal cord injury; spinal shock; surgical decompression